WNK4 restrains endometrial cancer progression by reprogramming macrophage polarization toward an M1-like phenotype - Jiarong He; Tian Zhang; Menglan Xiong; Jing Zhao; Ziqing Wan; Guang Li; Qi Tian; Pu Zhang; Chuqiang Shu (Molecular Biology Reports, 2026)

Long-term organic fertilization fosters modular microbial networks: A global analysis of soil bacteriome responses - Shu-Le Li; Cai Chen; Xiang-Yu Dai; Hai-Song Yan; Yao-Yang Xu; Meili Feng; Jun He; Jianfeng Ren; Wan-Ying Xie; Fang-Jie Zhao (Soil Ecology Letters, 2026)

Saebias A–G, eudesmane sesquiterpenes from Salvia plebeia with potential for Alzheimer's disease prevention via anti-neuroinflammatory and neuroprotective effects - Xiao-Die Shu; Han-Fei Liu; Yu-Qiong Liao; Wan-Jun Pu; Ting Zhao; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Exploration on the antigenicity evolution of β-lactoglobulin complexes: computer-driven novel ligand screening method, multispectroscopic analysis, in-depth interaction mechanism, and functional property characterization - Yang Xin; Yizhe Shang; Luyao Chen; Mengna Zhao; Yadan Ding; Guowei Shu; Xiuxiu Cui; Jianrui Chen; Hongchang Wan; Li Chen (Food Bioscience, 2026)

Ultrasound-activated endoplasmic reticulum-targeting piezoelectric nanoagonist with auxiliary intrinsic efficacy reverses tumor immunosuppression via spatiotemporal ICD in ovarian cancer - Shuangshuang Cheng; Haojia Li; Yuwei Yao; Ting Zhou; Wan Shu; Jiarui Zhang; Tangansu Zhang; Guanglei Zhong; Guanxiao Chen; Xiaoyu Shen; Yingying Peng; Shuyang Yu; et al. (Chemical Engineering Journal, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

Ultrastable Pt clusters confined on CeO2 nano-islands for efficient low-temperature propane dehydrogenation over carbon nanotube - Jian Tao; Shu-Lin Liu; Zi-Dan Li; Wan-Yi Wang; Chuan-Feng Huang; Bao-Lian Su; Zhao Wang (Chemical Engineering Journal, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Tinosporoside E and tinosporane A: two new clerodane diterpenes from the tuberous roots of Paratinospora sagittata - Li Fan; Yu-Jie Zhang; Shi-Peng Zhang; Wan-Shu Li; Ling-Juan Zhu; Hang-Juan Lin (Natural Product Research, 2026)

Unraveling the co-catalytic-adsorption mechanism of organic phosphonate degradation and simultaneous inorganic phosphorus removal in Fe Ce doped biochar/H2O2 system: Enhanced synergistic interface reactions - Chao Yu; Congcong Guo; Yuyou Li; Shu Yang; Mingjing Shi; Jun Wan; Jingwen Pan; Lei Wang; Baoyu Gao (Desalination, 2026)

Precise and high-throughput origin discrimination for green coffee beans by mass spectrometry-based metabolic analysis - Zifan Yang; Yuchen Feng; Zihang Yang; Ziqi Luo; Weikang Shu; Yanhui Wang; Bin Li; Ziheng Qi; Jingjing Wan (Food Research International, 2026)

Co-solvent-modulated polyamide nanofiltration membranes for high-temperature separation - Wan-Long Li; Xiao-Wei Luo; Wan-Ting Lin; Si-Yuan Zhang; Zi-Lu Zhang; Zi-Jun Zhang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2026)

Integrative transcriptomic and epigenomic analysis reveals the molecular mechanism of light-enhanced calcification in giant clams - Wenjie Yi; Fan Mao; Ke Wan; Shiwei Fu; Md. Abu Kawsar; Xiangcheng Yuan; Jun Li; Zhiming Xiang; Shu Xiao; Weihua Zhou; Ziniu Yu; Yang Zhang (Aquaculture, 2026)

Iridoid glycosides and phenolic glycosides from Gentiana rhodantha and their anti-inflammatory activities - Han-Fei Liu; Wan-Jun Pu; Ting Zhao; Xiao-Die Shu; Jun-Jie Lan; Chao Chen; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Variational microeukaryotic community diversity through wide-bound Antarctic water masses - Jiyuan Wan; Furong Cao; Wangxinze Shu; Zhengang Liu; Bin Kong; Dong Li; Xiao-hua Zhang; Qian Liu; Mingjian Liu; Xiaochong Shi; Yong Jiang (Marine Environmental Research, 2026)

Unraveling the impact of microplastics on autoimmune diseases: hidden dangers and environmental triggers - Yu-Tong Tan; Wei-Wei Wang; Shu-Zhen Xu; Yu-Wan Chang; Lei Li; Peng Wang; Hai-Feng Pan (Environmental Geochemistry and Health, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Bamboo-inspired self-descaling tubular evaporators with a Janus-confined water layer for rapid and durable hypersaline brine desalination - Yi-Zhou Chen; Ting Shen; Jia-Hui Xin; Yu Zhang; Kai Li; Ling-Shu Wan; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2025)

Revisiting the quantitative relationship between groundwater evapotranspiration and water table depth: A numerical study - Shu-Cong Tan; Xiao-Wei Jiang; Zhi-Yuan Zhang; Peng-Fei Han; Xu-Sheng Wang; Li Wan; Yi-Jian Zeng (Journal of Hydrology, 2025)

Bionics-inspired highly robust and fatigue-resistant hydrogel composite elastomers with multi-applications - Jiaxin Shen; Haizhou Huang; Chen Li; Huihui Shi; Shisheng Hou; Kuibo Yin; Hengchang Bi; Shu Wan; Litao Sun (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A Gln alteration influences leaf morphogenesis by mediating gibberellin levels in tobacco - Qi-Li Mi; Hong-Tao Lv; Fei-Fei Huang; Li Xu; Zi-Ying Huang; Wen-Wu Yang; Mei-Yun Zou; Hai-Tao Huang; Wan-Li Zeng; Jia-Yin Zhao; Qing-Xian Chen; Yong-En Si-Tu; et al. (Journal of Plant Physiology, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

ACE2 Rescues Sepsis-Associated Encephalopathy by Reducing Inflammation, Oxidative Stress, and Neuronal Apoptosis via the Nrf2/Sestrin2 Signaling Pathway - Ya Li; Tian-Tian Wan; Jia-Xin Li; Xue Xiao; Lei Liu; Hui-Hua Li; Shu-Bin Guo (Molecular Neurobiology, 2024)

Exploring the Potential of MIM-Manufactured Porous NiTi as a Vascular Drug Delivery Material - Yang Zhou; Tun Wang; Peng Lu; Zicheng Wan; Hao He; Junwei Wang; Dongyang Li; Yimin Li; Chang Shu (Annals of Biomedical Engineering, 2024)

Topological surface states in quasi-two-dimensional magnetic kagome metal EuTi3Bi4 - Zhicheng Jiang; Tongrui Li; Jian Yuan; Zhengtai Liu; Zhipeng Cao; Soohyun Cho; Mingfang Shu; Yichen Yang; Zhikai Li; Jiayu Liu; Jianyang Ding; Zhonghao Liu; et al. (Science Bulletin, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Development of an agroinfiltration-based transient hairpin RNA expression system in pak choi leaves (Brassica rapa ssp. chinensis) for RNA interference against Liriomyza sativae - Shu-Peng Li; Zi-Xu Chen; Ge Gao; Ya-Qi Bao; Wen-Ying Fang; Ya-Nan Zhang; Wan-Xue Liu; Marcé Lorenzen; Brian M. Wiegmann; Jing-Li Xuan (Pesticide Biochemistry and Physiology, 2024)

Rapid evaluation of the quality of Smilax glabra Roxb. using QADS based on FT-NIR combined with multiple intelligent algorithms - Geng-zhi Zhan; Xin-yue Guo; Zi-chao Qiu; Lu-yao Cai; Qian Hu; Ye Gao; Shu-wan Tang; Cun-yu Li; Yun-feng Zheng; Guo-ping Peng (Food Chemistry, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Deoxynivalenol and T-2 toxin cause liver damage and egg quality degradation through endoplasmic reticulum stress in summer laying hens - Haoneng. Guo; Hongyan Wan; Wenfang Lou; Rifat Ullah Khan; Jinming You; Bo Huang; Shu Hao; Guanhong Li; Sifa Dai (International Journal of Biometeorology, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Identification of SNPs and candidate genes associated with growth using GWAS and transcriptome analysis in Coilia nasus - Yue Yu; Shi-Ming Wan; Shuang-Meng Zhang; Jun-Qi Liu; Ai-Li Sun; Yao Wang; Yong-Fu Zhu; Shu-Xin Gu; Ze-Xia Gao (Aquaculture, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

The source of rock moisture in a sandstone cave in arid northern China: rainfall infiltration or vapor condensation? - Xiao-Wei Jiang; Kai-Gao Ouyang; Xu-Lin Tang; Shu-Cong Tan; Jia-Xin Shi; Na Li; Hong-Bin Yan; Jian-Guang Ren; Li Wan (Hydrogeology Journal, 2024)

Clarifying the correlations between hydraulic indicators evaluating the hydraulic performance of free water surface constructed wetlands - Di Wan; Yalong Li; Qing Zhu; Yuanlai Cui; Yonghong Shu; Changqiang Guo (Environmental Science and Pollution Research, 2024)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Acid-induced tubular g-C3N4 for the selective generation of singlet oxygen by energy transfer: Implications for the photocatalytic degradation of parabens in real water environments - Yu-Wei Li; Shu-Zhi Li; Min-bo Zhao; Li-Yan Liu; Zi-Feng Zhang; Wan-Li Ma (Science of The Total Environment, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Martynoside rescues 5-fluorouracil-impaired ribosome biogenesis by stabilizing RPL27A - Mengying Hong; Yushen Du; Dongdong Chen; Yuan Shi; Menglong Hu; Kejun Tang; Zhuping Hong; Xiangzhi Meng; Wan Xu; Gaoqi Wu; Yuanyuan Yao; Liubo Chen; et al. (Science Bulletin, 2023)

Genome size and GC content of myxomycetes - Shu Li; Bao Qi; Xueyan Peng; Wei Wang; Wan Wang; Pu Liu; Bao Liu; Zhanwu Peng; Qi Wang; Yu Li (European Journal of Protistology, 2023)

Drought adaptation of Bauhinia faberi var. Microphylla seedlings with dual inoculation of arbuscular mycorrhizal fungi - Xia Li; Wan-ze Zhu; Wen-wu Wang; Sheng-lan Ma; Zhe-liang Sheng; Shu-miao Shu (Journal of Mountain Science, 2023)

On the extinction depth of freezing-induced groundwater migration - Xiao-Wei Jiang; Hong-Yu Xie; Shemin Ge; Han Tang; Shu-Cong Tan; Xu-Sheng Wang; Li Wan; Yijian Zeng (Journal of Hydrology, 2023)

Evaluation of Fe3O4-MnO2@RGO magnetic nanocomposite as an effective persulfate activator and metal adsorbent in aqueous solution - Mang Lu; Xue-jiao Wu; Chu-xing Wan; Qiu-ping Gong; Jia-xin Li; Shuang-shuang Liao; Yu-an Wang; Shu-hao Yuan (Environmental Science and Pollution Research, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Huntingtin-associated protein 1 is a potential tumor suppressor for gastric cancer - Ye-Min Qu; Ai Chen; Xue Zhao; Zan Wang; Dong Guo; Shu-Li Shao; Yuan-Yong Tao; Qiu-Jing Li; Ming-Yi Wang; Wan-Shan Ma (Molecular Biology Reports, 2023)

Comparative analysis of cold-responsive genes under short-term cold stimulation and cold-adaptive genes under long-term heterogeneous environments reveals a cold adaptation mechanism in weeping forsythia - Yong Li; Shu-Chen Wang; Qian Li; Ming-Wan Li; Run-Li Mao; He-Chen Zhang; Wang-Jun Yuan; Jine Quan (Genetica, 2023)

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Solar-induced efficient propylparaben photodegradation by nitrogen vacancy engineered reticulate g-C3N4: Morphology, activity and mechanism - Yu-Wei Li; Zi-Feng Zhang; Shu-Zhi Li; Li-Yan Liu; Wan-Li Ma (Science of The Total Environment, 2023)

Enhanced preservation effects of clove (Syzygium aromaticum) essential oil on the processing of Chinese bacon (preserved meat products) by beta cyclodextrin metal organic frameworks (β-CD-MOFs) - Ying Wang; Yi-Tong Du; Wan-Yu Xue; Liang Wang; Rong Li; Zi-Tao Jiang; Shu-Hua Tang; Jin Tan (Meat Science, 2023)

Effects of furanic compounds from biomass pyrolysis on ketonization reaction: The role of oxygenated side groups - Wenran Gao; Yiling Wan; Shanhui Zhao; Muhammad Asif Akhtar; Kuan Ding; Bin Li; Yinlong Wu; Shoujun Zhang; Shu Zhang (Fuel, 2023)

Developing membrane reactors with suspended polyphthalocyanine nanoplatelets for upscaling syntheses of protein-polymer bioconjugates - Wen Fang Wei; Wan Lin Guo; Min Jian; Liu Shu Qin; Xue Li; Tao Cai (Chemical Engineering Journal, 2023)

Scholte wave dispersion and particle motion mode in ocean and ocean crust - Xu Xin; Wan Yong-Ge; Li Zhen-Yue; Sheng Shu-Zhong (Applied Geophysics, 2022)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Overexpression of PREX1 in oral squamous cell carcinoma indicates poor prognosis - Shu-Cheng Wan; Hao Wu; Hao Li; Wei-Wei Deng; Yao Xiao; Cong-Cong Wu; Lei-Lei Yang; Wen-Feng Zhang; Zhi-Jun Sun (Journal of Molecular Histology, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

Genetic analysis and fine mapping of the gall midge resistance gene Gm5 in rice (Oryza sativa L.) - Hailian Zhou; Xinyi Wang; Yi Mo; Yang Li; Liuhui Yan; Zhihua Li; Wan Shu; Ling Cheng; Fengkuan Huang; Yongfu Qiu (Theoretical and Applied Genetics, 2020)

MPTP-Induced Impairment of Cardiovascular Function - Xiaoli Liu; Bo Wei; Qianqian Bi; Qihang Sun; Li Li; Jian He; Yuancheng Weng; Shenyan Zhang; Genxiang Mao; Yizhong Bao; Shu Wan; Xiao Z. Shen; et al. (Neurotoxicity Research, 2020)

Identification of Biomarkers Related to Neuropathic Pain Induced by Peripheral Nerve Injury - Chun-guo Zhang; Hong-quan Wan; Ke-ning Ma; Shu-xin Luan; He Li (Journal of Molecular Neuroscience, 2019)

Antifungal Susceptibility Profile of Candida Albicans Isolated from Vulvovaginal Candidiasis in Xinjiang Province of China - Liang Yan; Xiao-dong Wang; Seyedmojtaba Seyedmousavi; Juan-na Yuan; Palida Abulize; Wei-hua Pan; Nong Yu; Ya-li Yang; Hai-qing Hu; Wan-qing Liao; Shu-wen Deng (Mycopathologia, 2019)

Ameliorative Effects of Selenium on Cadmium-Induced Injury in the Chicken Ovary: Mechanisms of Oxidative Stress and Endoplasmic Reticulum Stress in Cadmium-Induced Apoptosis - Na Wan; Zhe Xu; Tianqi Liu; Yahong Min; Shu Li (Biological Trace Element Research, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Lower Selenoprotein T Expression and Immune Response in the Immune Organs of Broilers with Exudative Diathesis Due to Selenium Deficiency - Tingru Pan; Tianqi Liu; Siran Tan; Na Wan; Yiming Zhang; Shu Li (Biological Trace Element Research, 2018)

The K+/H+ antiporter AhNHX1 improved tobacco tolerance to NaCl stress by enhancing K+ retention - Wei-Wei Zhang; Jing-Jing Meng; Jin-Yi Xing; Sha Yang; Feng Guo; Xin-Guo Li; Shu-Bo Wan (Journal of Plant Biology, 2017)

Selenium Deficiency Induces Autophagy in Immune Organs of Chickens - Pervez Ahmed Khoso; Tingru Pan; Na Wan; Zijiang Yang; Ci Liu; Shu Li (Biological Trace Element Research, 2017)

Overexpression of a phospholipase Dα gene from Ammopiptanthus nanus enhances salt tolerance of phospholipase Dα1-deficient Arabidopsis mutant - Hao Qiang Yu; Tai Ming Yong; Hong Jie Li; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Planta, 2015)

Study of the permeability in melting zone of South China Sea based on percolation theory - Ju-ying Wan; He-hua Xu; Yan-zhen Li; Wei-bing Shu (Marine Geophysical Research, 2015)

Peanut violaxanthin de-epoxidase alleviates the sensitivity of PSII photoinhibition to heat and high irradiance stress in transgenic tobacco - Sha Yang; De-Yun Meng; Lin-Lin Hou; Yan Li; Feng Guo; Jing-Jing Meng; Shu-Bo Wan; Xin-Guo Li (Plant Cell Reports, 2015)

Cloning and functional validation of molybdenum cofactor sulfurase gene from Ammopiptanthus nanus - Hao Qiang Yu; Yuan Yuan Zhang; Tai Ming Yong; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Plant Cell Reports, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Risk for estrogen-dependent diseases in relation to phthalate exposure and polymorphisms of CYP17A1 and estrogen receptor genes - Po-Chin Huang; Wan-Fen Li; Pao-Chi Liao; Chien-Wen Sun; Eing-Mei Tsai; Shu-Li Wang (Environmental Science and Pollution Research, 2014)

Expression Profile of Maize MicroRNAs Corresponding to Their Target Genes Under Drought Stress - Ying-Ge Wang; Ming An; Shu-Feng Zhou; Yue-Hui She; Wan-Chen Li; Feng-Ling Fu (Biochemical Genetics, 2014)

Haladaptatus pallidirubidus sp. nov., a halophilic archaeon isolated from saline soil samples in Yunnan and Xinjiang, China - Bing-Bing Liu; Wan-Yu Zhao; Xiao Chu; Wael N. Hozzein; Deene Manik Prabhu; Mohammed A. M. Wadaan; Shu-Kun Tang; Li-Li Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Identification of differentially expressed genes in American cockroach ovaries and testes by suppression subtractive hybridization and the prediction of its miRNAs - Wan Chen; Guo-Fang Jiang; Shu-Hong Sun; Yong Lu; Fei Ma; Bin Li (Molecular Genetics and Genomics, 2013)

RNA interference-mediated resistance to maize dwarf mosaic virus - Zhi-Yong Zhang; Ying-Ge Wang; Xiao-Juan Shen; Lei Li; Shu-Feng Zhou; Wan-Chen Li; Feng-Ling Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Morphological and molecular cytogenetic characterization of partial octoploid Tritileymus - Jing Wang; Xin-Hong Chen; Wan-Li Du; Ji-Xin Zhao; Jun Wu; Xue-Ni Cheng; Yu-Hui Pang; Qun-Hui Yang; Shu-Hui Liu; Jie Fu (Genetic Resources and Crop Evolution, 2013)

Development and identification of a wheat-Leymus mollis multiple alien substitution line - Ji-Xin Zhao; Wan-Li Du; Jun Wu; Xue-Ni Cheng; Yang Gao; Yu-Hui Pang; Xin-Hong Chen; Shu-Hui Liu; Qun-Hui Yang; Jie Fu (Euphytica, 2013)

An analytical investigation of a sequence of unusual springtime ozone episodes over metropolitan Taichung in 2007 - Wan-Li Cheng; Li-Wei Lai; Walter Den; Shu-Ying Wang; Pay-Liam Lin; Chueh-Ying Pai (Meteorology and Atmospheric Physics, 2012)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Volatile organic compounds decomposition using nonthermal plasma coupled with a combination of catalysts - T. Zhu; Y. D. Wan; J. Li; X. W. He; D. Y. Xu; X. Q. Shu; W. J. Liang; Y. Q. Jin (International Journal of Environmental Science and Technology, 2011)

Characterization of Five Putative Acyl Carrier Protein (ACP) Isoforms from Developing Seeds of Arachis hypogaea L. - Meng-Jun Li; Xing-Jun Wang; Lei Su; Yu-Ping Bi; Shu-Bo Wan (Plant Molecular Biology Reporter, 2010)

Registration of Micro-Computed Tomography and Histological Images of the Guinea Pig Cochlea to Construct an Ear Model Using an Iterative Closest Point Algorithm - Chia-Fone Lee; Gen-Jia Li; Shu-Yen Wan; Wen-Jeng Lee; Kai-Yuan Tzen; Chiung-Hsiang Chen; Yu-Lin Song; Yuan-Fang Chou; Yuh-Shyang Chen; Tien-Chen Liu (Annals of Biomedical Engineering, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Isolation and characterization of microsatellite markers for Cycas hainanensis C. J. Chen (Cycadaceae) - Min Zhang; Zheng-Feng Wang; Shu-Guang Jian; Wan-Hui Ye; Hong-Lin Cao; Peng Zhu; Ling Li (Conservation Genetics, 2009)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

Isolation and characterization of microsatellite loci in endangered Cycas changjiangensis (Cycadaceae) - Ling Li; Zheng-Feng Wang; Shu-Guang Jian; Peng Zhu; Min Zhang; Wan-Hui Ye; Hai Ren (Conservation Genetics, 2009)

Mineralogical and geochemical study of a newly discovered mafic granulite, northwest China: Implications for tectonic evolution of the Altay Orogenic Belt - Han‐Lin Chen; Zi‐Long Li; Shu‐Feng Yang; Chuan‐Wan Dong; Wen‐Jiao Xiao; Yoshiaki Tainosho (Island Arc, 2006)
A mafic granulite body was newly discovered in the Altay Orogenic Belt, northwest China. The rocks comprise a suite of coarse‐grained and fine‐grained granulites. Orthopyroxenes (hypersthenes) in the rocks have high X Mg and low Al 2 O 3 contents, whereas clinopyroxenes have low TiO 2 and Al 2 O 3 contents. Amphiboles and biotites have a high Mg/(Mg + Fe 2+ ) ratio and low contents of F and Cl. The peak metamorphic pressure–temperature (P–T) conditions are estimated as 750–780°C and 6–7 kbar, and retrograde P–T conditions are in the range of 590–620°C and 2.3–3.7 kbar, indicating significant decompression. Metamorphic reactions and P–T estimates define a clockwise P–T path. Geochemically, the rocks are high in Mg/(Mg + Fe) and Al 2 O 3 , depleted in U, Th, K and Rb, and characterized by light rare earth element enrichment and a weak positive Eu anomaly. The Altay mafic granulite shows depleted Nb, P and Ti contents in the mid‐oceanic ridge basalt normalized spider diagram. The geochemical characteristics suggest that the protolith of the Altay mafic granulite was calc‐alkaline basalt and andesite with an island‐arc affinity. The rock has a high 143 Nd/ 144 Nd ratio with ɛNd(0) > 0, indicating derivation from a mantle‐depleted source. In the present study, a two‐stage model for the evolution of the Altay mafic granulite is proposed: an early stage in which calc‐alkaline basalt and andesite with island‐arc affinity were subducted into a deeper level of the crust and subjected to granulite‐facies metamorphism generating the mafic granulite, followed by the later stage exhumation of the system into the upper crust by the late Paleozoic thrusting.